Harvesting, Storing, and Feeding Forages as Round Bale Silage - William E. Kunkle (EDIS)
This paper will review the research, experiences, and challenges of the round bale harvesting, storing, and feeding system. This document is AN145, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, UF/IFAS. Published October 2003.